The Influence of Halal Lebelization, Product Quality, Service Quality and Interest on Purchase Decisions and Increasing the Selling Value of Bakery and Chake, Padangsidimpuan City - Ade Khadijatul Z. HRP; Andri Soemitra; Zuhrinal M. Nawawi; Rahmat (PT Inovasi Pratama Internasional, 2022)
The community of Padangsidimpuan City consumes a lot of bakery and chake, which has increased market competitiveness and may have an impact on consumer purchasing decisions and product prices. In order to increase the selling value of the bakery and chake industry in Padangsidimpuan City, this research was undertaken to examine and assess the impact of halal labeling, product quality, service quality, and price on consumer purchase decisions. Quantitative descriptive research is used for the study, and multiple linear regression analysis is used for data analysis with the aid of the IBM SPSS version 23 program. The findings demonstrate a considerable favorable impact on consumer behavior of the independent variables halal labeling, product quality, service quality, and pricing.